2010
DOI: 10.1007/s00383-010-2571-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of retinoic acid and zinc on the treatment of caustic esophageal burns

Abstract: Zinc has not been found effective in the prevention of stricture formation. The results indicate that ATRA has a preventive effect in the development of fibrosis in an experimental model of caustic esophageal burns in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…[9] To reduce inflammation and collagen synthesis and to prevent fibroplasia and stricture formation, many clinical and experimental studies have evaluated the medical efficiency of antioxidant and anti-inflammatory agents, such as sucralfate, palifermin, dimethyl sulfoxide, prednisolon, retinoic acid, zinc, trapidil, trimetazidine, and pentoxifylline. [9][10][11][12][13]20,21] Despite decreased stricture formations in these studies, the rate of stricture formation remained at 70%-100% in highgrade corrosive esophagitis. [9] Garlic oil, a diallyl trisulfide, is the main active constituent of garlic and is one of the oldest medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] To reduce inflammation and collagen synthesis and to prevent fibroplasia and stricture formation, many clinical and experimental studies have evaluated the medical efficiency of antioxidant and anti-inflammatory agents, such as sucralfate, palifermin, dimethyl sulfoxide, prednisolon, retinoic acid, zinc, trapidil, trimetazidine, and pentoxifylline. [9][10][11][12][13]20,21] Despite decreased stricture formations in these studies, the rate of stricture formation remained at 70%-100% in highgrade corrosive esophagitis. [9] Garlic oil, a diallyl trisulfide, is the main active constituent of garlic and is one of the oldest medicine.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Although many agents have been used in various studies to prevent the stricture development, antibiotics and steroids have only recently gained clinical approval. [10][11][12][13] Garlic oil, a diallyl trisulfide, is the main active constituent of garlic. The beneficial effects of dietary garlic have been known for centuries.…”
Section: Introductionmentioning
confidence: 99%
“…Today, the aim of therapy in corrosive esophageal burn injuries is to prevent development of fibrosis, stricture formation, and perforation [4]. Several types of nonsurgical management such as steroid injections, antibiotics, esophageal dilatation, stent applications, and surgical treatment options are used for treatment [2, 46]; but current types of treatment are quiet ineffective for severe corrosive burns.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of nonsurgical management such as steroid injections, antibiotics, esophageal dilatation, stent applications, and surgical treatment options are used for treatment [2, 46]; but current types of treatment are quiet ineffective for severe corrosive burns. In experimental models, some agents such as vitamins E and C, heparin, mitomycin, penicillamine, caffeic acid, epidermal growth factor, interferon g, sphingosylphosphorylcholine, phenethyl ester, progesterone, and estradiol are found to be effective in different degrees [713].…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies in segments of rabbit esophageal mucosa showed that increasing pH levels and exposure times to NaOH led to an increase in cell membrane and tight junction damage [1]. Several studies on animal models have focused their attention on attenuating the oxidative damage induced by alkaline ingestion [18][19][20]. However, no studies have focused their attention on the possible culture of EECs after exposure to different concentrations of NaOH, for further applications of esophageal tissue engineering.…”
mentioning
confidence: 96%